The Effects of Emotional Intelligence on the Leadership Development of Undergraduate Students; Mentorship from MSIB MBKM as a Moderating Variable - Wibowo, Nadia Utami; Almahendra, Rangga; Mayasari, Dian (Universitas Gadjah Mada, 2024)
Introduction/Main Objectives: To investigate the impact of emotional intelligence on the development of effective leadership, with mentorship activities embedded within student's participating in Magang dan Studi Independen, Merdeka Belajar Kampus Merdeka (Certified Internship and Independent Study Merdeka Belajar Kampus Merdeka, MSIB MBKM) as a moderating element. Background Problems: Scholarly investigation on experiential learning has demonstrated its superior efficacy as a pedagogical approach compared to traditional lecture-based teaching methods. MSIB MBKM is created on this basis however, to date minimum research is available. Novelty: This study will generate insight to understand the moderating effects of mentoring in MSIB MBKM towards the relationship between emotional intelligence and leadership development. Methods: Hayes process model 1 was conducted to address the research questions. Secondary data was obtained from a questionnaire by the MBKM committee to monitor and evaluate the process of MBKM. The questionnaire was administered for 4 months and obtained 4,007 responses. Finding/Results: Emotional intelligence significantly affects the leadership development of undergraduate students (comparing t statistics value to t table value; 19,367 > 1,648). Evidently, an R value of 0,430 shows that there is a 43% relationship. Therefore, it has empirically demonstrated its major impact on the enhancement of leadership skills among undergraduate students. The additional moderating contributes 44.2% to the explanation of the variance effect of the aforementioned relationship. Conclusion: This study contributes to the development of a program model for leadership development by evaluating the complementary effects of emotional intelligence and mentoring activities on optimal leadership performance.